Lanthanum chromite based composite anodes for dry reforming of methane. (2nd August 2018) - Sarno, Caterina; Luisetto, Igor; Zurlo, Francesca; Licoccia, Silvia; Di Bartolomeo, Elisabetta
Abstract: Composite anodes containing La0.6 Sr0.4 CrO3-δ (LSCr) and Ce0.9 Gd0.1 O2 (GDC) infiltrated with 5 or 10 wt% Ni were investigated as potential catalysts for dry reforming of methane (DRM) reaction in methane rich mixtures. Powders were characterized and tested as catalysts for DRM reaction. Ni-infiltrated composite anodes were used for fuel cell tests and compared to Ni-free anodes. Electrochemical tests were performed in different gas mixtures to evaluate the anodic performance in externally reformed biogas (external reforming mode). The design of an external layer of composite anode achieved the internal DMR reaction (internal reforming mode). Graphical abstract: Image 1 Highlights: La0.6 Sr0.4 CrO3-δ, GDC and 5 or 10 wt% Ni composite anodes are proposed. Stable performance were measured in external reformed mixture. A double layer cell was designed for dry methane reforming (DMR) reaction.